Nephron sparing surgery for a patient with a complicated solitary functioning kidney and a giant pT3 renal cell carcinoma: A case report - Yu, Minghao; Zhou, Jiatong; Shangguan, Xun; Qian, Subo; Ding, Jie; Qi, Jun (Frontiers in Surgery, 2023)
Solitary functioning kidney (SFK) with renal cell carcinoma (RCC) is an imperative indication for nephron sparing surgery (NSS). Nevertheless, giant pT3 RCC mass (maximum diameter > 20cm) on the functioning side of patient with SFK is extremely rare, and it is controversial that NSS benefit for these patients more than radical nephrectomy (RN). We presented a case of a 71-year-old female patient with 20*16cm RCC mass on the SFK, who initially appeared with hematuria and acute urinary tract obstructive anuria caused by kidney calculi. The patient underwent the NSS treatment after our evaluation, and the 26-month follow-up of the patient revealed that the renal function had recovered to the abnormal state before the tumor formation. In addition, no relapse or metastasis were detected.